Off-farm labour supply and production efficiency of farm household in rural Southwest Nigeria - Adebayo M. Shittu (Agricultural and Food Economics, 2014)
This study examines the influence of off-farm employment on production efficiency of farm household in Southwest Nigeria. The study was based on primary data collected from a cross-section of 489 rural farm households, drawn by multi-stage random sampling from Ogun and Oyo States, in Southwest Nigeria. The data was analysed by descriptive and econometric techniques, including specification and estimation of a conditional revenue frontier and a production inefficiency equation. The results showed that 47.1% of the rural farm households had some of their members involved in off-farm activities with a typical member devoting 34.3% of his/her work efforts to off farm activities, while off farm activities contributed 27.6% of a typical farm household's labour income (N282, 263.54 in 2005/2006). Increase in off-farm labour supply was found to be associated with significant (p < 0.01) reduction in production in-efficiency among the rural farm households. The study also found that farm household production efficiency is significantly enhanced by increasing the share of tree crops and livestock in farm household farming activities, having access to land by leasing and operating a much more consolidated landholdings. However, remittances from rural out-migrants do not significantly affect rural farm household production efficiency.
Keywords: J2; Q1; R2; 330; Off-farm labour supply; Production efficiency; Nigeria